Complete genome sequence of the halophilic archaeon Haloferax volcanii PC0224, isolated from a solar saltern in Thailand - Manassanan Phatcharaharikarn; Pattarawan Ruangsuj; Thunwarat Songngamsuk; Parweenuch Santaweesuk; Marut Tangwattanachuleeporn; Kanokporn Srisucharitpanit; Prapimpun Wongchitrat; Montri Yasawong (BMC Genomic Data)
Abstract Objectives Haloferax volcanii is an extreme halophile belonging to the Haloferacaceae family that thrives in hypersaline environments. This study presents the complete genome sequence of the H. volcanii strain PC0224 isolated from a Thai solar saltern. Genomic data will enhance our understanding of circadian rhythm mechanisms and their evolutionary significance in extremophilic archaea. Data description The H. volcanii PC0224 genome comprises four circular sequences containing 3,773,977 bp and 66.16% GC content. Sequenced using Illumina and PacBio technologies and assembled with Hybracter, the genome contained 3,731 CDS, 6 rRNAs, 54 tRNAs, 2 ncRNAs, and 4 CRISPR arrays. This dataset enables the investigation of circadian rhythm regulatory systems and comparative genomic studies of temporal adaptation mechanisms in extremophilic archaea.